Aplikasi Pemesanan Menu Makanan Berbasis Web Resposive - munawarah; Zainul Arifin, Muhyiddin; Yaqin, Nurul (SAINTEKBU, 2022)
Mie Endess is a noodle shop in Jombang, specifically at Jalan Governor Suryo No 11 A Gg. II, Jombang Kec. Jombang. Mie Endess is a restaurant that has many customers. However, Mie Endess still uses the manual method for ordering food and drinks, where waiters use paper and pen/pencil as media to record and order food and drinks ordered by customers. Therefore we need a responsive web-based information system that can speed up the process of submitting order lists from customers. Field condition analysis was carried out through interviews and old-system literature studies. The analysis results of the food menu ordering application built on a web basis will be described using UML (Unified Modeling Language) notation, Activity Diagram, and ERD to be further implemented using the PHP programming language and database using MySQL. The Bootstrap Framework is also used from the application design side to provide application flexibility when accessed with devices with a smaller resolution. In addition, this application is equipped with a non-cash payment feature which is very efficient in payments.